2020
DOI: 10.2147/prbm.s282061
|View full text |Cite
|
Sign up to set email alerts
|

<p>Work-Related Stress and Associated Factors Among Textile Factory Employees in Northwest Ethiopia: A Cross-Sectional Study</p>

Abstract: Background: Work-related stress is becoming an alarmingly growing public health concern worldwide. Textile factories are among the most common manufacturing industries that have a higher rate of work-related stress. Investigating the prevalence and factors associated with work-related stress will help planners and decision-makers at every level in planning, managing, and evaluating the health status of the employees. Research evidence is limited for work-related stress in Northwest Ethiopia. Therefore, this st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
15
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(21 citation statements)
references
References 42 publications
4
15
1
Order By: Relevance
“…In the current study, current use of khat had a signi cant positive association with work-related stress among employees. The result observed in studies conducted at the bahirdar textile factory (14) and the amhara region, Ethiopia(48) is consistent with the nding. The time spent chewing khat may in uence the working time of the individuals and also as the employees spent more time chewing khat they might experience the feeling of guilty and self-blame, which leads to frustration and stress in the long run(48).…”
Section: Job Content and Clinical Characteristics Of Respondentssupporting
confidence: 84%
See 3 more Smart Citations
“…In the current study, current use of khat had a signi cant positive association with work-related stress among employees. The result observed in studies conducted at the bahirdar textile factory (14) and the amhara region, Ethiopia(48) is consistent with the nding. The time spent chewing khat may in uence the working time of the individuals and also as the employees spent more time chewing khat they might experience the feeling of guilty and self-blame, which leads to frustration and stress in the long run(48).…”
Section: Job Content and Clinical Characteristics Of Respondentssupporting
confidence: 84%
“…The Poor physical environment is the summed score of below 9. These instruments were used in a previous study conducted among bahirdar textile factory and dukem shoe factory employees in Ethiopia and it was valid and reliable (14,15). Screening Test for Alcohol, Smoking, and Substance (ASSIST Version 2.0) is made up of eight items that measure lifetime(Question 1 rated "yes" = 1/"no" = 0; interview stops if "no") and recent (past 3 months; question 2: interview continues for each substance used in the past 3 months only) of substance.…”
Section: Data Collection Tool and Proceduresmentioning
confidence: 99%
See 2 more Smart Citations
“…Our study demonstrated that HBP was associated with past-year suicidal ideation among currently employed individuals probably because of pressure at work [50,54] or work dissatisfaction [55], which may impair an individual's ability to cope, resulting in suicidal ideation. The findings are congruent with those in the literature [56]; however, the identification of currently employed individuals as a high-risk group for past-year suicidal ideation is unique.…”
Section: Discussionmentioning
confidence: 75%